Compilation of Evidence on COVID-19 Vaccine Immunization During Pregnancy and Breastfeeding - Solis-Pacheco, Josué; Rodríguez-Arreola, Ariana; Pérez-Montaño, Julia Aurora; Aguilar-Uscanga, Blanca Rosa (European Journal of Applied Sciences, 2024)
COVID-19 represented a public health problem for pregnant and breastfeeding women, and the question arose whether or not to continue breastfeeding. Various studies were carried out to elucidate whether or not breast milk from mothers in the COVID-19 pandemic and post-pandemic stages provided benefits to newborns. We collected information on PubMed, Scolar Google, Research Gate platforms about studies carried out on breastfed newborns from mothers infected with COVID-19, during pregnancy and after delivery. We used the scientific reports carried out between 2019 and 2023 show that a mother infected with COVID-19 or vaccinated does not harm the health of the infant, on the contrary, the consumption of human milk provides important immunological and neurological benefits to newborn babies. The results of these studies support vaccination as a useful clinical strategy to beneficially affect anti-SARS-CoV-2 IgG levels in the human milk. The reported research demonstrates that breast milk is safe and effective, even during times of illness in a mother infected with COVID-19, and provides protection to the infant when the mother has been vaccinated against COVID-19.